Community structure and biomass of tree species at Chini watershed forest, Pekan, Pahang - Khairil .M,; Wan Juliana .W.A,; Nizam .M.S,; Faszly .R, (Universiti Kebangsaan Malaysia, 2011)
A study was conducted to determine the tree species composition, diversity and estimate of above ground biomass at Chini watershed forest. Three types of forest were identified. Thirty plots of 0.1 ha were established in the inland, seasonal flood and riverine forests. A total of 3974 trees with diameter at breast height (dbh) at 5.0 cm and above were recorded. The inland forest recorded 2061 individuals representing 393 species from 164 genera and 57 families; the seasonal flood forest, 1019 individuals representing 268 species from 137 genera and 57 families; and the riverine forest, 894 individuals representing 260 species from 133 genera and 53 families. Endospermum diadenum (Euphorbiaceae), Streblus elongatus (Moraceae) and Aporusa arborea (Euphorbiaceae) was the most important species in the inland forest, seasonal flood forest and the riverine forest, with Importance Value Index (SIVi) of 3.36%, 4.43% and 2.96%, respectively. Euphorbiaceae was the most important family in the inland and riverine forest with FIVi of 14.25% and 12.91% and Myrtaceae in the seasonal flood forest at 12.36%. The Shannon-Weiner diversity index (H’) were considered high in all three forest types at 5.40 (H’max = 5.97) in the inland forest, 5.10 (H’max = 5.54) at the seasonal flood forest and 5.08 (H’max = 5.56) for the riverine forest. Shannon evenness index (J’) in the three types of forest was 0.9. The Sorenson’s community similarity coefficient (CCs) showed that tree species communities between the three forest types had low similarities with CCs= 0.4. The total above ground biomass estimated in the inland forest was 366.2 tan/ha, in the seasonal flood forest was 379.8 tan/ha and in the riverine forest was 401.1 tan/ha. A total of 44 endemic species in Peninsular Malaysia were found and 104 species were listed in the checklist of Conservation Status of Malaysian Trees that utilized the 2009 IUCN Red List Categories by World Conservation Monitoring Centre (WCMC).